Correlation between pseudotyped virus and authentic virus neutralisation assays, a systematic review and meta-analysis of the literature - Cantoni, Diego; Wilkie, Craig; Bentley, Emma M.; Mayora-Neto, Martin; Wright, Edward; Scott, Simon; Ray, Surajit; Castillo-Olivares, Javier; Heeney, Jonathan Luke; Mattiuzzo, Giada; Temperton, Nigel James (Frontiers in Immunology, 2023)
Background The virus neutralization assay is a principal method to assess the efficacy of antibodies in blocking viral entry. Due to biosafety handling requirements of viruses classified as hazard group 3 or 4, pseudotyped viruses can be used as a safer alternative. However, it is often queried how well the results derived from pseudotyped viruses correlate with authentic virus. This systematic review and meta-analysis was designed to comprehensively evaluate the correlation between the two assays. Methods Using PubMed and Google Scholar, reports that incorporated neutralisation assays with both pseudotyped virus, authentic virus, and the application of a mathematical formula to assess the relationship between the results, were selected for review. Our searches identified 67 reports, of which 22 underwent a three-level meta-analysis. Results The three-level meta-analysis revealed a high level of correlation between pseudotyped viruses and authentic viruses when used in an neutralisation assay. Reports that were not included in the meta-analysis also showed a high degree of correlation, with the exception of lentiviral-based pseudotyped Ebola viruses. Conclusion Pseudotyped viruses identified in this report can be used as a surrogate for authentic virus, though care must be taken in considering which pseudotype core to use when generating new uncharacterised pseudotyped viruses.